2005
DOI: 10.1111/j.1365-2141.2005.05481.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Rho‐family GTPase gene RHOF in lymphocyte subsets and malignant lymphomas

Abstract: Summary We have studied the expression of RHOF, a member of the Rho‐GTPase family, in an array of lymphoid cells and tissues. Previous microarray studies demonstrated RHOF upregulation in a subset of transformed follicular lymphomas. Real‐time quantitative polymerase chain reaction evaluated RHOF expression in lymphocyte subpopulations, and normal and malignant lymphoid tissue. Cells and tissues of B‐cell origin expressed higher RHOF levels than their T‐cell counterparts. Neoplastic cells and tissues of B‐cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…16) And the Rho GTPases have been reported to regulate the unlimited proliferation, invasion, and metastasis in some human tumors. 13,15) The RhoA signaling has been reported to be activated in the invasion or metastasis including, but not limited to, colorectal cancer, breast cancer, and prostate cancer. [28][29][30] In order to explore its pro-oncogenic role in cervical carcinoma, we manipulated the RhoA level in Hela cells by overexpressing or knockdowning RhoA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16) And the Rho GTPases have been reported to regulate the unlimited proliferation, invasion, and metastasis in some human tumors. 13,15) The RhoA signaling has been reported to be activated in the invasion or metastasis including, but not limited to, colorectal cancer, breast cancer, and prostate cancer. [28][29][30] In order to explore its pro-oncogenic role in cervical carcinoma, we manipulated the RhoA level in Hela cells by overexpressing or knockdowning RhoA.…”
Section: Discussionmentioning
confidence: 99%
“…Several Rho GTPases are upregulated in some human tumors, including RhoA, RhoC, Rac1, and so on. [13][14][15] And the upregulated Rho GTPases play their pro-oncogenic roles via stimulating cell cycle progression and regulating gene transcription, for example, in promoting Ras-induced transformation. 16) The induction of tumor vascularization is essential for tumors to grow beyond a certain size, and malignant cells release factors that promote angiogenesis from nearby pre-existing blood vessels.…”
mentioning
confidence: 99%
“…These include NF-kB, 18 BCL-11A, 19 BALassociated protein, 20 and RhoF. 21 Importantly, many proteins previously unknown to be expressed in tFL such as ribosomal S6 kinase, Wnt2 protein, betacatenin like protein1, and the eta (Z) isoform of protein kinase C (PKC) were identified in the FFPE sample.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that Rif is up-regulated in a subset of transformed FLs (follicular lymphomas), and a significant percentage of FLs transformed to an aggressive DLBCL (diffuse large Bcell lymphoma) [27]. Other research has revealed that Rif is deleted in early-stage mycosis fungoides, which is the most frequent form of cutaneous T-cell lymphoma [28].…”
Section: Rif and Lymphocyte Morphologymentioning
confidence: 98%